Integrasi nilai-nilai keteladanan Rasulullah dalam pembelajaran SKI untuk penguatan karakter siswa SD - Ferdianto, Yulian (Maliki Interdisciplinary Journal, 2026)
This study analyzes the integration of the exemplary values of Prophet Muhammad SAW into Islamic Cultural History (SKI) learning as a strategy to strengthen elementary students’ character. Rooted in concerns about declining moral behavior among children and the limited implementation of character education within SKI instruction, this library research explores theoretical concepts, historical foundations, and previous findings related to prophetic values, the Charter of Medina, and character-based learning approaches. The results indicate that integrating prophetic values—such as honesty, responsibility, tolerance, and social solidarity—can be effectively implemented through contextual learning, collaborative methods, school habituation programs, and well-structured learning tools. SKI learning enriched with Islamic moral values contributes significantly to shaping students’ character and helps transform historical content into meaningful and applicable lessons for daily life.